ENT 530 Social Media Portfolio: Hotz n Crunchz / Nor Fazilla Husna Sujono - Sujono, Nor Fazilla Husna (2021)
In the modem age, social media has been an important medium for industry as this allows business enterprise to build brand recognition. It also improves the company's business success and assists in meeting the desired goals. The key objective of the present study is to assess the position of social media marketing as an online marketer with a view of product. Social networking marketing refers to the method of obtaining on-line traffic or visibility via social media platforms. Many advertisers are running at a quick clip to tap into a new, normal potential. The dominant stream of social media is gone. For enterprises, this provides an extraordinary marketing opportunity that transcends conventional middlemen and links firms directly with consumers. Customer retention remains the primary aim of the advertisers. Marketers' focus is moving from delivering an advertisement to beginning to connect with consumers. In this sense, the position of the marketer is moving from batch and blast processing to the development of listening posts and dialog hubs in the consumer communities. The move from independent pureplay conventional networks to an interconnected multi-channel solution lets advertisers meet the complexity of new consumer demands through a wide variety of technologies and channels. Social networking marketing is a new age demand. Through the rise in the use of the Internet, this theory has been quite popular. Countries with technological edges are now capitalizing on this theory. Nowadays, social marketing technology works differently than most media to connect to public. Company organizations, having the production of products using social media to exercise their marketing communications.